2011
DOI: 10.1103/physrevlett.107.223202
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally Narrow, Long-Term Stable Optical Frequency Reference Based on aEu3+Y2SiO5Crystal at Cryogenic Temperature

Abstract: Using an ultrastable continuous-wave laser at 580 nm we performed spectral hole burning of Eu(3+):Y(2)SiO(5) at a very high spectral resolution. The essential parameters determining the usefulness as a macroscopic frequency reference, linewidth, temperature sensitivity, and long-term stability, were characterized using a H-maser stabilized frequency comb. Spectral holes with a linewidth as low as 6 kHz were observed and the upper limit of the drift of the hole frequency was determined to be 5±3 mHz/s. We discu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…Therefore the measured drift rate of 5 × 10 −18 s −1 is primarily due to the spectral hole. This drift rate is roughly an order of magnitude smaller than that of a typical room-temperature FabryPérot cavity, and is similar to that reported by Chen et al [24] for spectral holes in Eu 3+ :Y 2 SiO 5 . Figure 4 shows measurements of the frequency noise of a laser locked to a pattern of spectral holes in …”
supporting
confidence: 88%
See 1 more Smart Citation
“…Therefore the measured drift rate of 5 × 10 −18 s −1 is primarily due to the spectral hole. This drift rate is roughly an order of magnitude smaller than that of a typical room-temperature FabryPérot cavity, and is similar to that reported by Chen et al [24] for spectral holes in Eu 3+ :Y 2 SiO 5 . Figure 4 shows measurements of the frequency noise of a laser locked to a pattern of spectral holes in …”
supporting
confidence: 88%
“…as narrow as 122 Hz [21] and a lifetime of order 10 6 s at 4 K [22]. In addition, high-resolution spectroscopy has shown that the environmental sensitivity of 580 nm spectral holes in Eu 3+ :Y 2 SiO 5 to temperature, pressure, and accelerations are all smaller than that of Fabry-Pérot cavities [23,24]. Furthermore, the sensitivity to magneticfield fluctuations and perturbations to the spectral hole pattern due to side-holes and anti-holes are small enough to allow laser frequency stabilization at the 10 −17 fractional frequency level [25].…”
mentioning
confidence: 99%
“…Currently we are not able to create these high-quality combs due to the laser linewidth of 30 kHz. Recent high-resolution hole-burning experiments in Eu:Y 2 SiO 5 support that this is possible [41].…”
Section: Discussionmentioning
confidence: 96%
“…The most widespread scheme relies on the stabilisation of the laser frequency to a high-finesse and super-stable optical Fabry-Pérot resonator by means of the Pound-Drever-Hall frequency stabilisation scheme [46]. An interesting alternative to this approach has recently been investigated, where the laser is stabilised to spectral holes burnt into an ensemble of Eu dopant ions in a solid at cryogenic temperatures [47][48][49]. Another method with high potential has been proposed that uses an active light source based on having alkaline-earth atoms in an optical lattice.…”
Section: Ultra-stable Lasers For Interrogation Of the Clock Transitionmentioning
confidence: 99%